A new method to realize high-throughput protein crystallization in a superconducting magnet. Issue 6 (27th November 2014) - Huang, Lin-Jun; Cao, Hui-Ling; Ye, Ya-Jing; Liu, Yong-Ming; Zhang, Chen-Yan; Lu, Qin-Qin; Hou, Hai; Shang, Peng; Yin, Da-Chuan
Abstract : We present a new method for the realization of high-throughput protein crystallization screening using an array of 96 capillaries aligned in a circle. In this method, each capillary represents a single crystallization condition, and all capillaries experience an identical magnetic field condition. Abstract : We present a new method for the realization of high-throughput protein crystallization screening using an array of 96 capillaries aligned in a circle. In this method, each capillary represents a single crystallization condition, and all capillaries experience identical magnetic field conditions. After crystallization, the crystals in the capillary can be directly diffracted without harvesting. This method proved easy to perform and is applicable for use in magnetic fields and may be further extended for use in other circumstances, for example, under space microgravity conditions.